PENGARUH MOTIVASI KERJA DAN KOMUNIKASI ORGANISASI TERHADAP DISIPLIN KERJA PERAWAT PADA RSUD BANGKINANG - Sari, Novita; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of work motivation and organizational communication on the work discipline of nurses in RSUD Bangkinang.the objek of this study was nurses at bangkinang district hospital with a sample of 58 people calculated using the slovin formula.The study concluded that the results of the t thest showed that work motivation on employee work discipline had a significant influence on employee work discipline n nurses at bangkinang district hospital. T test results showed that organizational communication on employee work discipline had a significant influence on employee work discipline in nurses at Bangkinang District Hospital. The f-test results show that work motivation and organizational communication simultaneously have a significant effect on accepted work discipline.Keywords : Keywords : work motivation, organization communication, work discipline